The Impact of Pancasila Student Profile and Rahmatan Lil 'Alamin Student Profile program at Madrasah Tsanawiyah - Partono; Shofiyatul Ulya; Majdy Kasheem (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2025)
A Clean school environment is an important element in the educational process. The role of students in maintaining cleanliness and developed trhought the implementation of the project for strengthen the profile of pancasila students and the profile of rahmatan lil ‘alamin students . the objectives of this research implementation stratrategy, to find out the supporting and inhibiting factor and to understand the impact of implementation of the project for strengthening the profile of pancasila students and the profile of rahmatan lil ‘alamin students. This research is field research with qualitative methods taking the object of study at MTs NU Ibtidaul Falah , data collection methods use are observation , interviews and documentations. The research result shoe that : strategies go through three stages; planning, implementation, and avaluation stage. inhibiting factors as follows; time, faunding, and understanding of pancasila and rahmatan lil alami value. Supporting factors ; enthusiastic students, availability of facilities, support from educators , support from parents and the community. Impact on students character of the P5 and P2RA values is as follows; faith, piety and bnoble character, mutual cooperation, civility, tolerance, example and equality.